Management of thyroid disorders: from autoimmunity to malignancy – novel insights from precision medicine - Katerina Saltiki; Grigoris Effraimidis (Drugs in Context, 2026)
This Editorial introduces the series How to manage thyroid diseases: from autoimmunity to malignancy Special Issue: https://www.drugsincontext.com/special_issues/how-to-manage-thyroid-diseases-from-autoimmunity-to-malignancy